2019
DOI: 10.2147/dddt.s220719
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hongjingtian Injection Inhibits Proliferation and Migration and Promotes Apoptosis in High Glucose-Induced Vascular Smooth Muscle Cells</p>

Abstract: BackgroundHongjingtian injection (HJT) is administered in the treatment of vascular diseases, including diabetic angiopathies (DA). However, its underlying mechanisms have not been examined systematically.MethodsIn this research, we explored potential mechanisms of HJT through network pharmacology. HG-stimulated A7r5 cells served as the cell model. Cell proliferation, migration and apoptosis were investigated. The effects on key targets and the AKT pathway were verified by Western blotting in experiments with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…VSMCs could undergo phenotypic transformation and increase their ability to migrate and proliferate through upregulation of the ERK1/2 and PI3K/Akt signaling pathways stimulated by high glucose ( Shi et al, 2015 ). In a similar study, Fan et al showed that the injection of hong jing tian could improve proliferation and migration by inhibiting the Akt pathway in high-glucose-induced vascular smooth muscle cells ( Fan et al, 2019 ). In addition, Zhou et al found that arctiin could attenuate the proliferation and arrest the cell cycle in the G0/G1 phase by inactivating VEGF and the PI3K/Akt signaling pathway in high-glucose-induced human retinal capillary endothelial cells ( Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…VSMCs could undergo phenotypic transformation and increase their ability to migrate and proliferate through upregulation of the ERK1/2 and PI3K/Akt signaling pathways stimulated by high glucose ( Shi et al, 2015 ). In a similar study, Fan et al showed that the injection of hong jing tian could improve proliferation and migration by inhibiting the Akt pathway in high-glucose-induced vascular smooth muscle cells ( Fan et al, 2019 ). In addition, Zhou et al found that arctiin could attenuate the proliferation and arrest the cell cycle in the G0/G1 phase by inactivating VEGF and the PI3K/Akt signaling pathway in high-glucose-induced human retinal capillary endothelial cells ( Zhou et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrin deposition is inhibited by the released inflammatory factors to suppress the fibrinolytic system, which contributes to the formation of the prethrombotic state (27). High glucose concentration-induced ERS results in the dysfunction of endothelial cells, the inhibition of cell proliferation and cell death, thereby contributing to injury to vessels and various vascular diseases, including diabetic vascular disease (28,29). Autophagy, apoptosis, inflammation and senescence of endothelial cells can be induced by high dosage of glucose (30).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes (T2D) is associated with chronic inflammation, characterized by the production of pro-inflammatory factors like TNF-a, IL-a, FGF21, and PDGF at sites of high glucose exposure. This inflammatory response involves pathways such as PI3K/Akt and NF-kB, contributing to VSMC de-differentiation, proliferation, and migration, which can trigger the additional release of pro-inflammatory agents by the VSMCs themselves, worsening vascular dysfunction [ 67 , 103 , 104 , 105 , 106 , 107 , 108 , 109 ]. Additionally, VSMCs in individuals with T2D exhibit increased expression of the antiapoptotic protein Bcl-2, leading to resistance to cell death, enhanced proliferation, and a thicker media layer [ 110 ].…”
Section: Vascular Smooth Muscle Cell Phenotype Switching In Diseasementioning
confidence: 99%